[980-72-145+6-(14+a)]-119=842
Răspunsuri la întrebare
Răspuns de
4
Explicație pas cu pas:
[ 980 - 72 - 145 + 6 - ( 14 + a ) ] - 119 = 842
[ 980 - 72 - 145 + 6 - ( 14 + a ) ] = 842 + 119
[ 980 - 72 - 145 + 6 - ( 14 + a ) ] = 961
[ 908 - 145 + 6 - ( 14 + a ) ] = 961
[ 763 + 6 - ( 14 + a ) ] = 961
[ 769 - ( 14 + a ) ] = 961
769 - 14 + a = 961
755 + a = 961
a = 755 - 961
a = - 206
Răspuns de
2
908-145+6-14-a=842+119
763+6-14-a=961
769-14-a=961
755-a=961
755-961=a
-206=a
a=-206
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă